2015
DOI: 10.4236/ojo.2015.57025
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Triquetrum Fractures: The Importance of Proper Roentgenograms in Ulnar Sided Wrist Pain

Abstract: Triquetrum fractures are the second most common carpal fractures after scaphoid. However they are seldom encountered due to their clinical symptoms and since they cause less functional disability. They can be misdiagnosed as soft-tissue injuries by considering the similar localization of pain and prolonged symptoms. The majority of triquetrum fractures can be diagnosed with direct X-ray. Obtaining three plane (anterior-posterior, lateral and oblique) X-rays is especially important in diagnosing dorsal chip fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, Welling et al . [ 19 ] found that 20% of triquetral fractures were hidden on plain radiographs whereas Ozdemir et al [ 20 ] and Beccet et al [ 14 ] highlighted the role of oblique views plus CT and MRI scans in contrast for proper diagnosis. In our case, the standard views pointed out the presence of a triquetrum fracture and the subsequent CT scan revealed this uncommon pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Welling et al . [ 19 ] found that 20% of triquetral fractures were hidden on plain radiographs whereas Ozdemir et al [ 20 ] and Beccet et al [ 14 ] highlighted the role of oblique views plus CT and MRI scans in contrast for proper diagnosis. In our case, the standard views pointed out the presence of a triquetrum fracture and the subsequent CT scan revealed this uncommon pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal chips that remain symptomatic for a long period can be excised surgically [ 21 ]. Undisplaced, body fractures, can be treated conservatively with cast immobilization [ 20 ]; in cases of marked displacement open reduction and internal fixation with a compression screw and/or Kirschner wires may be required [ 6 , 22 ]. Non-union is rare but can be successfully treated with late ORIF [ 23 ].…”
Section: Discussionmentioning
confidence: 99%